2020
DOI: 10.1128/msystems.00660-19
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Plateau Environment on the Gut Microbiota and Blood Clinical Indexes in Han and Tibetan Individuals

Abstract: The intestinal microbiota is significantly affected by the external environment, but our understanding of the effects of extreme environments such as plateaus is far from adequate. In this study, we systematically analyzed the variation in the intestinal microbiota and 76 blood clinical indexes among 393 healthy adults with different plateau living durations (Han individuals with no plateau living, with plateau living for 4 to 6 days, with plateau living for >3 months, and who returned to the plain for 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 28 publications
3
56
0
Order By: Relevance
“…The highly active β-galactosidase in Solobacterium provides nutrients for Prevotella, and promotes biofilm production (Barrak et al 2020). Solobacterium and Prevotella produce H 2 S, which regulates human blood pressure and pulmonary arterial pressure, increases cerebral blood flow, and helps the host adapt to a low-pressure hypoxic environment (Chen et al 2020;Mishra et al 2020b;Prabhakhar and Joyner 2014). The present study found that Gemella was positively correlated with Streptococcus, but negatively correlated with Prevotella.…”
Section: Changes In the Network Topological Features With Altitudesupporting
confidence: 51%
See 2 more Smart Citations
“…The highly active β-galactosidase in Solobacterium provides nutrients for Prevotella, and promotes biofilm production (Barrak et al 2020). Solobacterium and Prevotella produce H 2 S, which regulates human blood pressure and pulmonary arterial pressure, increases cerebral blood flow, and helps the host adapt to a low-pressure hypoxic environment (Chen et al 2020;Mishra et al 2020b;Prabhakhar and Joyner 2014). The present study found that Gemella was positively correlated with Streptococcus, but negatively correlated with Prevotella.…”
Section: Changes In the Network Topological Features With Altitudesupporting
confidence: 51%
“…Tibetans also have the EPAS1 , EGLN1 , and PPARA genes related to adaptation to the plateau, which help the body to better adapt to the harsh environment (Zhou et al 2013 ; Huerta-Sánchez et al 2014 ; Lou et al 2015 ). Many bacteria in the Tibetan intestinal microbiota produce short-chain fatty acids, which promote energy metabolism and homeostasis of the intestinal microbiota (Jia et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4b ). These two genes are involved in signalling via GPCR and insulin receptor signalling pathways, which play critical roles in the hypoxia response 28,29 ; indeed, both insulin and glucose levels are reduced in Tibetan individuals relative to Han individuals 30 . These findings indicate gene-regulatory roles of dbsv57015 through the deactivation of a gene-regulatory enhancer element with combined effects on multiple genes.…”
Section: Resultsmentioning
confidence: 99%
“…However, host's GM can be affected by various factors. Besides unchangeable internal genetic background [ 7 ], unique external geography environment characteristics, including regional altitude, also are important factors interacting with the GM of body [ 8 , 9 ]. Qinghai-Tibet Plateau, as a high-altitude area in China, is well known for its poor environmental characteristics, such as low atmosphere oxygen, cold and dry weather, and high intensity of ultraviolet radiation.…”
Section: Introductionmentioning
confidence: 99%